Online versus In-Person Services: Effects on Patients and Providers - Amanda Dahlstrand; Nestor Le Nestour; Guy Michaels (Institute of Labor Economics (IZA), 2024)
Online delivery of one-to-one services offers potential cost savings and increased convenience, yet relatively little is known about its impacts on providers and consumers. This paper studies the online delivery of healthcare, focusing on primary care doctor consultations. We use novel data from Sweden and an effectively random assignment of patients to nurses, who differ in their propensity to direct patients to online versus inperson consultations. Our findings reveal that online consultations are delivered sooner, are shorter, and yield similar in-consultation outcomes, including rates of diagnosis, prescriptions, and specialist referrals, as well as patient satisfaction. However, in the short term, online consultations lead to more emergency department (ED) visits and additional in-person primary care visits, though no significant medium-term health effects are observed. We discuss the extent to which follow-ups reduce online's cost savings, as well as online's advantages for different patients and how to improve hybrid organizations' cost effectiveness.
Keywords: J44; I11; O33; 330; telehealth; remote work; online services